STRES PERAWAT INDONESIA DI MASA PERUBAHAN - Nadita, Niken; Mata, Shinta Dwiyanti; Juniarta; Sampepadang, Mega (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Stress has both positive and negative effects on nurses. Changes in the hospital's management and systems necessitate nurses to adjust to the hospital's new policies, work culture, and environment, which can be stressful. In addition, nurses’ workloads may be impacted during the change and transition, increasing their stress levels. This study aimed to describe the stress levels of head nurses and nursing staff during a hospital’s transitional period. The research employed a quantitative descriptive cross-sectional design. This study used a purposive sampling method, recruiting 44 registered nurses. Inclusion criteria were those who have worked for at least one year under the current management system. Utilizing the Indonesian version of the Bianchi Stress Questionnaire, this study measured levels of work-related stress (Alpha Cronbach 0,974). This study was conducted midway through 2019. A descriptive statistic is used to measure the nurses’ level of stress. The results of this study, 37.5 percent of head nurses (n=16) experienced mild stress and severe stress during the transition period, with personnel management (M = 3.8; SD = 1.99) and unit management (M = 3.8; SD = 1.97) being the most intense stressors. In addition, 53.58 percent of nursing staff experienced severe stress, with interpersonal relationships constituting the most intense stressor (M = 4.48, SD = 1.35). Despite stress from various subscales, this study provides evidence that during the transition period, head nurses and nursing staff can experience mild to severe stress levels, and the recommendation for future research is to investigate the contributing factors of stress in nurses.